(4x-8)-(7x-9)=

Simple and best practice solution for (4x-8)-(7x-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-8)-(7x-9)= equation:


Simplifying
(4x + -8) + -1(7x + -9) = 0

Reorder the terms:
(-8 + 4x) + -1(7x + -9) = 0

Remove parenthesis around (-8 + 4x)
-8 + 4x + -1(7x + -9) = 0

Reorder the terms:
-8 + 4x + -1(-9 + 7x) = 0
-8 + 4x + (-9 * -1 + 7x * -1) = 0
-8 + 4x + (9 + -7x) = 0

Reorder the terms:
-8 + 9 + 4x + -7x = 0

Combine like terms: -8 + 9 = 1
1 + 4x + -7x = 0

Combine like terms: 4x + -7x = -3x
1 + -3x = 0

Solving
1 + -3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -3x = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -3x = 0 + -1
-3x = 0 + -1

Combine like terms: 0 + -1 = -1
-3x = -1

Divide each side by '-3'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| (64u^6v^12)^1/3 | | (7/24)/(1/6) | | 8(v+3)-2v=2(3v+4)-13 | | 2x^2-2x-6=x^2-x-4 | | f+8squared=3squared | | x-13x=3x-6 | | 36=12x+x^2 | | y=-x+6x-12 | | a(5)=6 | | 3+11x-1=9x+29-7x | | 4.9x-10x/3-12 | | 12x=9x+342 | | 8x+19=6x+34 | | 5x^2+17x-17=3-4x | | (14x^7-16x^3)/2x^3 | | x+(x*.22)=275 | | 4X+43=2X+69 | | (2*x-10/3)*(5/6*x-30) | | (2x-10/3)x(5/6x-30) | | 26x=64 | | (3v-7)(5-v)=0 | | (7x^2+2)(4x^2-19x-5)=0 | | 5k-10/12/6k | | 4(5x-4)+6=-4 | | 4h=220m | | (2x+3)(3x^2-13x+12)=0 | | y=6-2/3y | | 220m=4h | | 25x^2+14x+49=0 | | V/18=u | | 5x-55=6x-42 | | 2/3(1/2x+12)=1/2(1/3x+14)-3 |

Equations solver categories